The Conflict between Mining Law and Anti-Corruption Law in Indonesia’s Extractive Sector: A Study of Legal Justification and Judicial Reasoning - Pandiangan, Marolop; Harkrisnowo, Harkristuti; Nelson, Febby Mutiara (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2026)
Corruption in Indonesia’s extractive industry has generated significant state revenue losses, regulatory distortions, and environmental harm. A key legal issue arises from the concurrent use of the Anti-Corruption Law and the Mineral and Coal Mining Law in addressing offenses within the sector, raising questions regarding legal certainty and the proper application of the lex specialis principle. This study examines the legal justification for applying the Anti-Corruption Law to mining-related offenses, analyzes judicial reasoning in relevant court decisions, and formulates a framework for criminal policy reconstruction. This research employs a normative legal method, combining statutory, conceptual, and case approaches. It critically analyzes legislative frameworks alongside selected judicial decisions to identify patterns of interpretation and enforcement. The study further situates these findings within theories of lex specialis, legal certainty, and utilitarian deterrence. The results demonstrate that the application of the Anti-Corruption Law is often justified by courts based on broader notions of state financial loss and deterrence objectives. However, this approach has led to interpretative inconsistencies, particularly in distinguishing between administrative violations under mining law and criminal acts qualifying as corruption. Such inconsistencies reflect an unresolved tension between sector-specific regulation and general anti-corruption enforcement. This study argues that the core issue lies not merely in normative overlap, but in the absence of clear doctrinal boundaries and coherent judicial standards. Accordingly, it proposes regulatory harmonization, strengthened interpretative guidelines, and an integrated criminal policy framework that combines penal, administrative, and restorative mechanisms to promote legal certainty, accountability, and sustainable governance in Indonesia’s extractive industry